2016
DOI: 10.1038/bjc.2016.322
|View full text |Cite
|
Sign up to set email alerts
|

TTP as a surrogate endpoint in advanced hepatocellular carcinoma treated with molecular targeted therapy: meta-analysis of randomised controlled trials

Abstract: Background:Time to progression (TTP) is suggested as a reliable endpoint compared with the progression-free survival in the clinical trials of hepatocellular carcinoma (HCC). However, the correlation between TTP and overall survival (OS) has never been studied.Methods:We searched PubMed and Embase data to obtain data source. Eligible studies were randomised controlled phase III trials, which evaluated the efficacy of systemic chemotherapy or molecular targeted therapy in advanced HCC. The association of treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
0
11
1
Order By: Relevance
“…The sole meta-analysis, including nine RCTs, specifically assessing TTP as a surrogate endpoint of OS at advanced stages of HCC showed a medium strength correlation between treatment effects on TTP and OS (r = 0.73). 626 Discordant signals keep emerging in very recent randomised phase II trials at intermediate and advanced stages. 560 All these data support revisiting TTP as a reliable endpoint in HCC research.…”
Section: Time To Progressionmentioning
confidence: 99%
“…The sole meta-analysis, including nine RCTs, specifically assessing TTP as a surrogate endpoint of OS at advanced stages of HCC showed a medium strength correlation between treatment effects on TTP and OS (r = 0.73). 626 Discordant signals keep emerging in very recent randomised phase II trials at intermediate and advanced stages. 560 All these data support revisiting TTP as a reliable endpoint in HCC research.…”
Section: Time To Progressionmentioning
confidence: 99%
“…Additionally, the improvements in PFS and OS in the Japanese REACH-2 subpopulation were consistent with those observed for ramucirumab in the subpopulation of Japanese patients with AFP C 400 ng/mL (n = 42) in the REACH study (PFS HR 0.261, 95% CI 0.391-0.986; OS HR 0.464, 95% CI 0.232-0.926) [21]. As death due to liver cirrhosis can confound the potential benefits of the investigational drug, PFS and TTP are suggested as surrogate endpoints in phase 3 trials for patients with advanced HCC treated with molecular targeted therapy, with a threshold of HR B 0.6 for PFS and TTP being suggestive of improvement in OS [22,23]. In the current analysis, the improvements in PFS and TTP (which reflect the antitumor effects of the investigational drug per se, whereas OS may be confounded by postdiscontinuation therapy) were marked, with an HR of 0.282 and 0.248, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [29] concluded that TTP can be a surrogate endpoint for OS based only on the finding of a good correlation between TTP (or PFS) HR and OS HR; however, it is important to consider the objective of a clinical trial in addition to the correlation between TTP HR and OS HR when we evaluate the applicability of using TTP as a surrogate marker for OS. On one hand, we can certainly predict the OS HR from data on the TTP HR, as described above for an early-stage trial with the aim of judging as to whether there is value in proceeding to a pivotal trial.…”
Section: Discussionmentioning
confidence: 99%